2016
DOI: 10.1177/1463949115627906
|View full text |Cite
|
Sign up to set email alerts
|

Creating dialogues: Exploring the ‘good early childhood educator’ in Chile

Abstract: The aim of this study was to explore the different ways in which a number of Chilean stakeholders conceptualise the 'good early childhood educator' in Chile. In a context where new foreign narratives are increasingly dominating the field and the recent standardisation of the educators' professional role is being implemented, this research constitutes a critical and alternative viewpoint, analysing the situation as a whole and creating dialogues between key actors in order to open possibilities to new understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
1
3
0
2
Order By: Relevance
“…In concordance with the previous evidence in Chile, the findings obtained show that early childhood teachers perceive that their professional identity is contravened to a significant degree by other actors in the field (Castillo, 2017;Viviani, 2016), with particular emphasis given to the perception of schoolification as a threat to their professional identity (Pardo & Woodrow, 2014). It is interesting to observe that these findings do not appear to be singular to Chile, since other countries in Latin America and Europe report schoolification and government policies as challenges to the professional identity of early childhood teachers (Dalli, 2017;López, 2013;Sarceda Gorgoso, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In concordance with the previous evidence in Chile, the findings obtained show that early childhood teachers perceive that their professional identity is contravened to a significant degree by other actors in the field (Castillo, 2017;Viviani, 2016), with particular emphasis given to the perception of schoolification as a threat to their professional identity (Pardo & Woodrow, 2014). It is interesting to observe that these findings do not appear to be singular to Chile, since other countries in Latin America and Europe report schoolification and government policies as challenges to the professional identity of early childhood teachers (Dalli, 2017;López, 2013;Sarceda Gorgoso, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…In Chile, Viviani (2016) found that early childhood teachers understood their professional role, contradicting the view of representatives of the provider institutions. Specifically, while the representatives show that early childhood teachers lack specialized knowledge, they consider themselves capable or suitably qualified despite this.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…For Viviani (2016), female practitioners are expected to have a strong vocation, to always be joyful and love their children. Love and joy can be linked to Froebel’s philosophy (Peralta, 2012), in which female practitioners’ essence is assumed to be closer to nature and therefore also to children.…”
Section: Duerme Duerme Negrito Que Tu Mama Está En El Campo (…) Y Smentioning
confidence: 99%